Recent Status of Coral Reef Ecosystem in Penuktukan Bali, Indonesia: the Implication for Sustainable Marine Tourism Implementation - Linda Herawati; Luchman Hakim; Guntur Guntur (Journal of Indonesian Tourism and Development Studies, 2016)
Recent development of marine tourism in Penuktukan Village, Sub district Tejakula of the Buleleng Regency in Bali has been contributed to the coral reef ecosystem. The aim of the research was to determine the coral reefs coverage, coral reef and fishes diversity  inPenuktukan Villages, Sub district Tejakula of the Buleleng Regency. Result of the research confirms that coral reef coverage in Penuktukan was varied from 53 to 56%, indicates human impact to coral reefs ecosystems. The coverage level can be influenced by tourist activities.Based on the observation it is clear that Coral Foliose types were dominant.Diversity index (H’) of coral reefs ranging from 1.754 to 1.814; while the evenness index (E) was ranging from 0.8435 to 0.9468. The observed fish was less than 25 individual.These fishes taxonomically belong to Serranidae,  Lutjanidae,  Letherinidae, Caesionidae, Scaridae, Haemulidae and  Chaetonodae.It was lowest compared to the standard for population in healthy water. The implementation of marine based tourism in Penuktukan Village should be controlled through visitor management and coral reef ecosystem conservation.Keywords: Bali, coral reefs, marine tourism.